CYBERFEMINISM ON MAGDALENE.CO FROM A GENDER JOURNALISM PERSPECTIVE - Fadillah, Siti Nurul; Putri, Sekar (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Magdalene can be said to be an advocacy for the protection of women's rights and voices in the form of Cyberfeminism. A platform that exists online emerged because of dissatisfaction with reports related to the image of women by the media. Magdalene.co has a column that discusses women's violence, equality, relationships, LGBT issues, and other feminist content from a gender journalism perspective. Not only that, this official website also often reviews several published articles about women and looks at the media's position in reporting them. The urgency of this research will certainly bring a new perspective to be analyzed regarding the reporting of women's images in the mass media, by considering data via the online media Magdalene.co. regarding feminism and the issue of sexual violence against women and the position of the media in reporting it according to Sara Mills' theory based on social reality. The results of the research show that the discourse in the online media coverage of Magdalene.co has a complete bias towards women and is in accordance with the feminist ideology implemented by Magdalene.co to the point that it is used as cyberfeminism. Journalists at Magdalene.co publish articles or reports with the aim of protecting women while adhering to journalistic ethics.